2011
DOI: 10.1007/s12028-011-9626-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin, Levetiracetam, and Pregabalin in the Acute Management of Refractory Status Epilepticus in Patients with Brain Tumors

Abstract: Background There were nearly 700,000 patients in the United States in 2010 living with brain tumor diagnoses. The incidence of seizures in this population is as high as 70% and is historically difficult to control. Approximately 30-40% of brain tumors patients who present with status epilepticus (SE) will not respond to typical therapy consisting of benzodiazepines and phenytoin (PHT), resulting in patients with refractory status epilepticus (RSE). RSE is usually treated with anesthetic doses of propofol or mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 22 publications
0
20
1
3
Order By: Relevance
“…39 For patients with SE who have primary or metastatic brain tumours, treatment with phenytoin or leveti racetam as first-line antiepileptic drugs (AEDs) and pregabalin as a second-line AED was found to control epilepsy in 70% of cases, with 0% mortality in responders. 40 History of epilepsy Results from a study of a rural Chinese cohort showed that the risk of premature death in people with convulsive Box 1 | Outcome factors in SE: demographics, aetiology and clinical characteristics…”
Section: Acute Aetiologymentioning
confidence: 99%
“…39 For patients with SE who have primary or metastatic brain tumours, treatment with phenytoin or leveti racetam as first-line antiepileptic drugs (AEDs) and pregabalin as a second-line AED was found to control epilepsy in 70% of cases, with 0% mortality in responders. 40 History of epilepsy Results from a study of a rural Chinese cohort showed that the risk of premature death in people with convulsive Box 1 | Outcome factors in SE: demographics, aetiology and clinical characteristics…”
Section: Acute Aetiologymentioning
confidence: 99%
“…26 Swisher et al suggested that the combination use of PHT, LEV, and pregabalin (PGB) in brain tumor patients with refractory status epilepticus is safe and highly effective. 27 As demonstrated by these cases, we proposed that LEV may be a useful AEDs for seizure induced by LE. And this application did not have an obvious psychiatric adverse side effect.…”
Section: Discussionmentioning
confidence: 88%
“…The researchers concluded that LTG penetrates well into brain and tumor tissue and had a moderately high protein binding (15). It has been shown that pregabalin has been used as adjunctive therapy in this subgroup of patients although limited data are available, which is the case with most other newer agents (16). …”
Section: Role Of Anticonvulsants In Acute Seizure Management and Seizmentioning
confidence: 99%
“…There were no adverse reactions to Trifecta reported. The authors concluded that in patients with brain tumors presenting in RSE that Trifecta use is highly effective and safe (16). …”
Section: Seizure Management With Levetiracetammentioning
confidence: 99%